2020
DOI: 10.31729/jnma.5411
|View full text |Cite
|
Sign up to set email alerts
|

Cases of Left Against Medical Advice from the Emergency Department of a Tertiary Care Hospital in Kathmandu: A Descriptive Cross-Sectional Study

Abstract: Introduction: Left against medical advice is a worldwide phenomenon. Patients leaving against Left against medical advice do not provide the health professionals with legal impunity. A well-informed consent should be present with surety that they are well understood by the patient before they leave. The study was undertaken to study the prevalence of patients that leave against medical advice. Methods: This is a descriptive cross-sectional study done in the emergency department of a tertiary care hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Although LAMA is a global phenomenon, it is quite high in Nepal and India and the most common reasons were financial limitations and anticipated poor prognosis. 23,24 There was only single in-hospital mortality in our study. A likely explanation for this finding is that patients often opt for LAMA in cases with anticipated poor prognosis.…”
Section: Discussionmentioning
confidence: 54%
“…Although LAMA is a global phenomenon, it is quite high in Nepal and India and the most common reasons were financial limitations and anticipated poor prognosis. 23,24 There was only single in-hospital mortality in our study. A likely explanation for this finding is that patients often opt for LAMA in cases with anticipated poor prognosis.…”
Section: Discussionmentioning
confidence: 54%
“…Recent Nepalese studies from the ICU and emergency departments have reported the prevalence of LAMA to be 14.5% and 5.96% respectively. [10][11][12][13][14][15] Though our study excluded patients from the emergency department, the rate of LAMA in our study was comparable to it but less than a similar Nepalese study carried out in the ICU. The rate of neurosurgical LAMA-related discharge was higher in our study when compared to other in-patient departments across a wide range of studies.…”
Section: Discussionmentioning
confidence: 59%
“…It is also most likely to admit patients with chronic, serious illnesses requiring prolonged hospitalization and advanced cases which were referred from other hospitals in rural and sub-urban areas. Previous studies have postulated that these patients often refuse to stay in the hospital for a long time 3 as do patients presenting with non-specific complaints such as chest pain, headache, nausea and vomiting who require extensive workup in an internal medicine unit to rule out more serious conditions [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…LAMA is associated with increased litigation risk and poses a dilemmatic ethical and legal problem for clinicians. It is a big challenge in developing countries like Pakistan where problems of staff shortage, lack of insurance and centralization of healthcare services predominate the clinical scenario 3 .…”
Section: Introductionmentioning
confidence: 99%